Measuring Student Satisfaction In Using Learning Management System At ED-TECH Company - Sandy Anugerah; Astari Retnowardhani (Jurnal Mantik, 2022)
Nowadays, technology and education have a strong relationship. Especially in this pandemic situation which forced people to work and study from home. The education world does not only talk about formal education such as school or college. Many students or employees searching for informal education to develop their skills. Education technology companies offer educational services that are combined with technology to enable the online teaching and learning process. This process supports the current condition which we need to keep learning in the middle of social distancing. This case study aims to evaluate student satisfaction with the learning management system while studying at an education technology company. This research uses IS Success Model to find is there any direct influence from technical system quality, service quality, educational system quality perceived usefulness, and information quality to the user satisfaction toward learning management system. This research took a sample of 70 students at one of the ed-tech companies in Indonesia who already used the learning management system in this company for at least 1 month for their study. The result showed that perceived usefulness and technical system quality are significantly affected user satisfaction.